Methodology for the synthesis of NP25302 and other bioactive natural products - Stevens, K (2011)
Total synthesis of the pyrrolizidine alkaloid NP25302: (+)-NP25302 is an unusual vinylogous urea containing pyrrolizidine alkaloid shown to exhibit cell adhesion inhibition. It was envisaged that this natural product could be accessed by a novel 5-endo-dig cyclisation to construct the pyrrolizidine core, and a Curtius rearrangement to install the vinylogous urea motif. This methodology was first tested on a model system, furnishing nor-NP25302 from L-proline in 12 steps and 9% overall yield. The total synthesis of (±)-NP25302 was completed in 9 steps and 26% overall yield from ethyl 2-nitropropionate using similar methodology. Studies into the stereospecificity of the Au(I)-catalysed cyclisation of monoallylic diols: During the synthesis of (+)-isoaltholactone in the Robertson group, the key Au(I)-catalysed cyclisation was observed to occur with some stereospecificity. Further investigations were therefore conducted into the stereochemical outcome of this reaction using stereodefined allylic alcohols, and from the combined results a mnemonic was proposed to predict the stereochemistry of the products of this reaction. Studies into the total synthesis of ascospiroketals A and B: Investigations were conducted into the total synthesis of the recently isolated natural products ascospiroketals A and B. A second generation synthesis was used to construct advanced intermediates 1 and 2.